Massive Aggregations of Serpulidae Associated With Eutrophication of the Mar Menor, Southeast Iberian Peninsula - Sandonnini, Jessica; Del Pilar Ruso, Yoana; Cortés Melendreras, Emilio; Giménez Casalduero, Francisca (Frontiers in Marine Science, 2021)
For decades, nutrients and organic matter inputs to the Mar Menor coastal lagoon have favoured the change from an original oligotrophic state to a eutrophic state. The lagoon reached a stage of severe eutrophication and "environmental collapse" during the spring of 2016. This paper describes the massive growth of Serpulidae (Annelida, Polychaeta) forming large aggregations and reef structures following the environmental collapse caused by the 2016 eutrophication crisis. Four species belonging to the genera Hydroides Gunnerus, 1768 and Serpula Linnaeus, 1758 were identified; the identified species are Hydroides elegans (Haswell, 1883), Hydroides dianthus (Verrill, 1873) , Serpula concharum (Langerhans, 1880) and Serpula vermicularis (Linnaeus, 1767). The presence of bi-operculate and tri-operculate specimens is also documented in this study.